Didactic strategies in a program of Bachelor of Early Childhood Education (Encuentros, 2021)
This article presents the results of the research "Description of didactic strategies implemented in the teaching-learning processes by teachers of the Bachelor of Early Childhood Education Program". Developed from a qualitative approach with educational action research design. As a result, the teaching styles of the teachers who participated in this research were described, from categories of the constructivist and traditional approach, in order to find the didactic strategies and their relationship with the pedagogical model of the IES where the research was developed. The existence of coherence between the strategies implemented with what was proposed in the pedagogical model is concluded and a possible route is proposed to mediate learning processes, according to the findings.